Difluorocarbene-Based Cyanation of Aryl Iodides - Zhang, Yin-Xiang; Xiao, Xuan; Fu, Zhi-Hong; Lin, Jin-Hong; Guo, Yu; Yao, Xu; Cao, Yu-Cai; Du, Ruo-Bing; Zheng, Xing; Xiao, Ji-Chang (Synlett, 2020)
A large number of efficient cyanation methods have been developed because of the wide range of applications of nitriles, but conventional methods usually suffer from the need for a toxic cyanation reagent. Although difluorocarbene chemistry has received increasing attention, the use of difluorocarbene as a sources of the nitrile carbon for nitrile groups remains largely unexplored. We describe a difluorocarbene-based cyanation of aryl iodides promoted by a cheap copper source, Cu(NO3)2·2.5H2O, under an air atmosphere. Ph3P+CF2CO2–, an easily available and shelf-stable difluorocarbene reagent, and NaNH2 are used as the carbon source and the nitrogen source for the nitrile group, respectively. The cyanation protocol is attractive because no toxic reagent is used and performing the reactions under an air atmosphere is operationally convenient.
Keywords: difluorocarbene; cyanation; nitriles; copper; aryl iodides